(192) PUBLIC ENTERPRISE IN ECONOMIC DEVELOPMENT: Its Scope, Organization Forms in General and The Indian Experience المؤسسات العامة في التنمية الاقتصادية: نطاقها، وأشكال التنظيم بشكل عام، والتجربة الهندية - Solomon, Jairaj (INP, 2025)
42 p paper